DEVELOPMENT OF MATHEMATICS LEARNING MEDIA WITH SNAKE AND LADDER GAME ON THE CIRCLE MAIN DISCUSSION - Mafrudlatun Nikmah; Uswatun Khasanah (Universitas Ahmad Dahlan, 2019)
The mathematic concept can be presented in a game snake and ladder to make it more interesting, more interactive. It can increase the students' quality of study, yet learning media used in school is minimal. Minimal research aims to develop mathematic learning media with snake and ladder game on the circle main discussion central circle in the third grade of junior high school that is proper for the mathematic learning process. This research is counted as research and development using the ADDIE model consisting of five phases: analysis, design, development, implementation, and evaluation. The research subjects The specialist subjects media specialist, students of Junior High School (SMP) Muhammadiyah 1 Minggir Sleman Regency, and State Junior High School (SMP Negeri) 3 Gamping Sleman Regency. Data analysis technique The qualitative data analysis is changed to be quantitative values using a Likert scale. Data collection technique The data this research used observation, interview, and questionnaire. Â The product of learning media developed is in the form of a compact disk (CD) that has gone through scoring and validating by three mathematic learning subject experts and three experts of mathematic learning media. The result from the subject experts is in the category of very good. The result from the media experts is in the very good category, and the result of students' responses is in a suitable category. Based on the results, it can be concluded that the learning media that is developed is proper to be used in the mathematic leering process.